Detection of minimal residual disease in acute myeloid leukemia: evaluating utility and challenges - Álvarez, Noemí; Martín, Alejandro; Dorado, Sara; Colmenares, Rafael; Rufián, Laura; Rodríguez, Margarita; Giménez, Alicia; Carneros, Laura; Sanchez, Ricardo; Carreño, Gonzalo; Rapado, Inmaculada; Heredia, Yanira; et al. (Frontiers in Immunology, 2024)
This study discusses the importance of minimal residual disease (MRD) detection in acute myeloid leukemia (AML) patients using liquid biopsy and next-generation sequencing (NGS). AML prognosis is based on various factors, including genetic alterations. NGS has revealed the molecular complexity of AML and helped refine risk stratification and personalized therapies. The long-term survival rates for AML patients are low, and MRD assessment is crucial in predicting prognosis. Currently, the most common methods for MRD detection are flow cytometry and quantitative PCR, but NGS is being incorporated into clinical practice due to its ability to detect genomic aberrations in the majority of AML patients. Typically, bone marrow samples are used for MRD assessment, but using peripheral blood samples or liquid biopsies would be less invasive. Leukemia originates in the bone marrow. This study aimed to assess the utility of cell-free DNA (cfDNA) from peripheral blood samples for MRD detection in AML patients. A cohort of 20 AML patients was analyzed using NGS, and a correlation between MRD assessment by cfDNA and circulating tumor cells (CTCs) in paired samples was observed. Furthermore, a higher tumor signal was detected in cfDNA compared to CTCs, indicating greater sensitivity. Challenges for the application of liquid biopsy in MRD assessment were discussed, including the selection of appropriate markers and the sensitivity of certain markers. This study emphasizes the potential of liquid biopsy using cfDNA for MRD detection in AML patients and highlights the need for further research in this area.